40‐3: Distinguished Paper: Realization of Ultra‐High Efficient Fluorescent Blue OLED. Issue 1 (28th June 2022) - Tasaki, Satomi; Nishimura, Kazuki; Toyoshima, Hiroaki; Masuda, Tetsuya; Nakamura, Masato; Nakano, Yuki; Itoi, Hiroaki; Kambe, Emiko; Kawamura, Yuichiro; Kuma, Hitoshi
Abstract : The bilayer structure for an emitting layer (EML) was developed to improve performances of a fluorescence blue organic light emitting diode. By functionally separating the EML into the charge recombination and the Triplet‐Triplet Fusion (TTF) zone, we successfully suppressed the quenching of triplet excitons by excess carriers to make more TTF efficient and the local degradation within the EML to make the lifetime longer. In the bottom emission device with the bilayer EML, 12% of external quantum efficiency (EQE) and 450 hours of LT95 were achieved. Furthermore, we achieved over 14% of EQE by optimizing the material combinations.